Engaging school students for enabling water security: Systemic challenges and search for opportunities - Coonghe, P.A.D.; Srikanthan, S.; Shivany, S.; Karthiga, I.; Dishalini, V. (University of Jaffna, 2022)
Student engagement is one of the key means to enhance water security in developing countries where water crisis is a prominent issue for the development of the regions. In terms of water security, educational and policy interventions at the school system level can drive the goals of water security and sustainability in water usage. The multifaceted relationship among education system, water pollution, waste management and environmental squalor requires multiple initiatives for ensuring water security in the Northern Province (NP) of Sri Lanka. As a step towards making NP secure for cleaner water consumption, a community-based action research project was set to foster the development of a model for engaging students whom in turn would enable water security. The present study attempted to analyze the opportunities and systemic challenges in engaging school students for water security in the NP of Sri Lanka. The data for this study were collected through systematic interactions using the World Café as a method for discussion with selected stakeholders of the educational sectors in the three divisions of the NP: Nallur, Kopay and Akkarayan.
Keywords: Security; Water stakeholders; School students; World café discussions; Northern Province; Sri Lanka